2013
DOI: 10.1097/bth.0b013e3182a5cbf8
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Spanning Plate Fixation for Distal Radius Fractures

Abstract: In polytrauma patients, the presence of a multifragmentary distal radius fracture poses a challenge with respect to early mobilization. Dorsal spanning plate fixation is an alternative choice for these patients for providing definitive operative fixation of the distal radius fracture and for providing a construct to allow weight-bearing through the injured wrist for rehabilitative purposes. In this article, we describe the operative technique to place a dorsal spanning plate and provide a retrospective review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…This technique was first described by Burke and Singer, 34 and serves simultaneously as a dorsal buttress and as a distraction device that bridges the fracture site to restore length and alignment, while avoiding complications from prolonged external fixation. 35 Overall, this study confirmed that dorsal spanning plates are an excellent alternative for surgical management of highenergy fractures in polytrauma patients. 36 During the period of review, Dodds et al 35 described the surgical technique of spanning plate fixation and reviewed outcomes in polytrauma patients.…”
Section: Dorsal Spanning Platessupporting
confidence: 74%
See 1 more Smart Citation
“…This technique was first described by Burke and Singer, 34 and serves simultaneously as a dorsal buttress and as a distraction device that bridges the fracture site to restore length and alignment, while avoiding complications from prolonged external fixation. 35 Overall, this study confirmed that dorsal spanning plates are an excellent alternative for surgical management of highenergy fractures in polytrauma patients. 36 During the period of review, Dodds et al 35 described the surgical technique of spanning plate fixation and reviewed outcomes in polytrauma patients.…”
Section: Dorsal Spanning Platessupporting
confidence: 74%
“…If comminution does not allow reconstruction and requires rapid but stable fixation, distraction plating with an internal dorsal spanning bridge plate can adequately restore length and alignment. 36 During the period of review, Dodds et al 35 described the surgical technique of spanning plate fixation and reviewed outcomes in polytrauma patients. 35 A major advantage of this technique is immediate unrestricted use of the hand, making it ideal for polytrauma patients with associated injuries.…”
Section: Dorsal Spanning Platesmentioning
confidence: 99%
“…15 Hardware failure in the bridge plating group often occurred after 8 weeks, which would be anticipated to have occurred after the fracture had healed. 6,10,18 Since patients treated with Bridge Plate will undergo a planned secondary procedure for hardware removal, hardware failure in this group has less clinical significance if it occurs after fracture union. Complex regional pain syndrome occurred at a higher rate in the ExFix group and was commonly treated with therapy.…”
Section: Discussionmentioning
confidence: 99%
“…13,31 The plate may be applied in a retrograde or antegrade fashion below the extensor tendons of the dorsal forearm and hand. 12,14 K-wires or interfragmentary screws may be used to augment the construct to stabilize articular fragments if necessary. 13,31 Burke and Singer originally used a 3.5 mm steel dynamic compression plate or single-or double-stacked one-third tubular plates as neutralization constructs.…”
Section: Developmentmentioning
confidence: 99%
“…These plates are produced by multiple manufacturers and are available in 2.4, 2.7, 3.2, and 3.5 mm sizes. 12,23…”
Section: Developmentmentioning
confidence: 99%